Increasing rate of daptomycin non-susceptible strains of Staphylococcus aureus in patients with atopic dermatitis - Błażewicz, Izabela; Jaśkiewicz, Maciej; Piechowicz, Lidia; Neubauer, Damian; Nowicki, Roman; Kamysz, Wojciech; Barańska-Rybak, Wioletta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Daptomycin is a cyclic lipopeptide that is bactericidal against Staphylococcus aureus , including methicillin-resistant S. aureus (MRSA), vancomycin-intermediate S. aureus (VISA) and vancomycin-resistant S. aureus (VRSA) strains. Daptomycin exerts its antimicrobial effect by a calcium-dependent interaction with the cytoplasmic membrane resulting in depolarization, ion loss and rapid cell death. Unfortunately, loss of daptomycin susceptibility in S. aureus in the clinical setting has been noted. Aim : To evaluate the susceptibility profile to daptomycin among S. aureus strains isloted from patients with atopic dermatitis (AD). Another point was to correlate the results obtained by broth microdilution method and Etest, which is commonly applied in clinical setting. Material and methods : One hundred patients with the diagnosis of atopic dermatitis were microbiologically assessed for the carriage of S. aureus . Antimicrobial susceptibility tests were performed using broth-microdilution (BMD) and Etests for daptomycin. Results : Staphylococcus aureus strains were isolated from the majority of our patients, either from the skin (73%) or the anterior nares (75%). Six of the 100 nasal swabs (6%) and 5 of the 100 skin swabs (5%) were positive for methicillin-resistant Staphylococcus aureus (MRSA). A total of 81 of 148 (54.7%) daptomycin non-susceptible isolates of S. aureus were identified by BMD. Only 19 of 81 were also classified as non-susceptible by Etest. Conclusions : Clinicians and microbiologists should be aware of the possibility of the emergence of daptomycin non-susceptibility (or increase in minimal inhibitory concentration) during prolonged therapy and closely monitor the susceptibility of persisting isolates that might be recovered during therapy.